จิตลักษณะ ปัจจัยภายในและปัจจัยภายนอกของครอบครัว ที่เกี่ยวข้องกับ การรับรู้วิธีการอบรมเลี้ยงดูในนักเรียนชั้นมัธยมศึกษา - สนามเขต(Trongkamon Sanamkate), ตรงกมล; พันธุมนาวิน (Duchduen Bhanthumnavin), ดุจเดือน (Journal of Behavioral Science for Development, 2016)
(Psychological Characteristics, Internal and External Familial Conditions as correlate of Perceived Appropriated Child-Rearing Practices in Thai Junior Highschool Students.) Abstract This research was a correlation-comparative study, based on the Interactionism model as a conceptual framework. Sample was 595 junior highschool students in 8th grade from 4 schools in school of Metropolis Bangkok and outer province school. It was comprised of 282 male students (47.5%) and 312 female students (52.5%) 2) school location, 283 students (47.6%) attended school in Metropolis Bangkok, and the rest of 311students (52.4%) were in outer province. Multistage random sampling method was employed to obtain the participants. Data were analyzed in total sample group as well as subgroups, categorized according to demographic characteristics. Regression Analysis revealed that all 12 predictors from the groups of psychological traits, external and internal familial conditions, and psychological states, were accounted for perceived love-oriented child-rearing practice with 37.0% and perceived reason-oriented child-rearing practice (30.4%) in the total sample. For intance, the four most common predictors were favorable attitudes toward parents, parent-child relation, social support from significant others, and psychological immunity. Furthermore, the art-risk groups of students who reported less perceived love and reasoning-oriented child-rearing practices were female students, students in Bangkok schools. The protective predictors of perceived child-rearing practices were favorable attitudes toward parents, parent-child relation, social support from significant others, and psychological immunity Keywords: Psychological characteristics, External and Internal Familial Conditions, Perceived love and reasoning-oriented child-rearing practices